零件信息组合中几何规则和模糊推理研究 - 李光荣; 胡升平; 王志亮; 鲁泳 (Jixie chuandong)
The methods of geometry rule and fuzzy reasoning integrating with alphabeticin tree theory are used to recognize the part information of STEPAP214 file.Geometry rule of typical surface combination are analyzed and determined.The feasibility analysis of part information characteristic combination recognization by using fuzzy reasoning is carried out.Several combination situations of fuzzy theory are defined according to actual situation.